The Roles of Leadership Styles in Corporate Social Responsibility - Du, Shuili; Swaen, Valérie 1975-; Lindgreen, Adam; Sen, Sankar (2013)
This research investigates the interplay between leadership styles and institutional corporate social responsibility (CSR) practices. A large-scale field survey of managers reveals that firms with greater transformational leadership are more likely to engage in institutional CSR practices, whereas transactional leadership is not associated with such practices. Furthermore, stakeholder-oriented marketing reinforces the positive link between transformational leadership and institutional CSR practices. Finally, transactional leadership enhances, whereas transformational leadership diminishes, the positive relationship between institutional CSR practices and organizational outcomes. This research highlights the differential roles that transformational and transactional leadership styles play for a firm’s institutional CSR practices and has significant implications for theory and practice.
Keywords: organizational outcomes; Stakeholder-oriented marketing; Transactional leadership; Transformational Leadership; Corporate Social Responsibility